(untitled) (GESTIÓN Y TENDENCIAS, 2020)
This article summarizes the experience that the Retirement Savings Laboratory (LAR) of the Inter-American Development Bank (IDB) has developed over its four years of existence in promoting voluntary pension saving in countries such as Chile, Colombia, Mexico, and Peru.